THE EFFECT OF SPIN-OFF POLICY AND MACROECONOMIC FUNDAMENTAL FACTORS ON THIRD PARTY FUNDS AT SHARIA GENERAL BANKS - Fatima Tuzzahara Alkaf; Nana Nawasiah (Pusat P2M Politeknik Negeri Batam, 2021)
In enhancing the development of Islamic banking, the government issued Law No. 21 of 2008 concerning spin-off. With this policy, it is expected that Islamic Commercial Banks will develop. This study aims to implement panel data regression to examine in depth the influence of spin-off policy and macroeconomic fundamental factors on third party funds of Sharia General Banks. Sampling by purposive sampling, six (6) Sharia General Banks that have conducted spin-offs and financial report data from 2014-2018. The Chow Test and the Hausman Test show that the panel data regression model that matches the variable data used in 2014-2018 is the Random Effect Model (REM). Empirical results show that during the 2014-2018 period, the spin-off policy and macroeconomic fundamental factors had a significant effect on the bank's third-party funds simultaneously. Partially, only the spin-off policy has a significant effect on third party funds.